A system-based framework for carbon emission and sequestration accounting at the village level: Evidence from rural China - Hong, Jingjing; Wang, Xinxin; Chen, Kevin Z. (CGIAR System Organization, 2025)
Against the backdrop of China’s “dual carbon” targets, villages represent a critical yet underexplored unit for linking national carbon neutrality goals with rural revitalization and grassroots climate governance. Existing carbon accounting studies have predominantly focused on macro-scale regions or individual sectors, often overlooking the integrated functioning of production, living, and ecological subsystems at the village level. In particular, the frequent omission of ecosystem-based carbon sinks has led to systematic biases in the assessment of rural net emissions. This study develops a system-oriented village-level carbon accounting framework grounded in systems theory, conceptualizing the village as a quasi-autonomous social–ecological system in which production, household activities, and ecological components are tightly coupled. Methodologically, the framework integrates emission factor–based accounting for multiple carbon source pathways—such as energy use, agricultural production, household consumption, and construction activities—with a systematic estimation of ecosystem carbon sinks. Key carbon sink processes, including forest biomass, bamboo stands, cropland, and soil carbon sequestration, are explicitly incorporated to capture the ecological regulation of village-level carbon balances. By constructing a closed-loop accounting structure encompassing carbon sources, carbon sinks, and net emissions, the framework provides a comprehensive representation of village-level carbon metabolism. While maintaining empirical feasibility through the use of accessible activity data and standardized emission factors, the framework is also capable of capturing indirect and upstream emission chains induced by local production and consumption activities, thereby enhancing the systemic completeness of the accounting results. An empirical application is conducted in Qingshan Village, Hangzhou, Zhejiang Province, based on a village-wide household survey and official administrative data for 2023. The results indicate that total annual carbon emissions amount to 14,469.05 t CO₂-eq, primarily driven by energy consumption and construction-related activities, whereas total carbon sequestration reaches 16,775.32 t CO₂-eq, largely contributed by forests, bamboo stands, and cropland ecosystems. Overall, Qingshan Village exhibits a net negative carbon balance, representing a typical case of a carbon-negative village. This study advances village-scale carbon accounting by systematically integrating carbon sources and ecosystem-based carbon sinks within a systems-theoretical framework. It provides a scientifically robust and operationally feasible basis for assessing rural carbon balances and offers methodological support for designing targeted and equitable mitigation strategies under China’s rural carbon neutrality agenda.